2023
DOI: 10.21037/qims-23-513
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic and epigenetic factors in determining the risk of spinal fragility fractures: new insights in the management of spinal osteoporosis

Vratko Himič,
Nikolaos Syrmos,
Gianfranco K. I. Ligarotti
et al.

Abstract: Osteoporosis predisposes patients to spinal fragility fractures. Imaging plays a key role in the diagnosis and prognostication of these osteoporotic vertebral fractures (OVF). However, the current imaging knowledge base for OVF is lacking sufficient standardisation to enable effective risk prognostication. OVF have been shown to be more prevalent in Caucasian patient cohorts in comparison to the Eastern Asian population. These population-based differences in risk for developing OVF suggest that there could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Additionally, there is a growing body of literature suggesting that the conventional DXA cutoffs, i.e., t -score > −1.0 for normal bone density, t -score −1.0 to −2.5 for osteopenia/low bone density, and t -score < −2.5 for osteoporosis, may apply differently to different racial backgrounds. Specifically, some groups have suggested that these conventional DXA cutoffs apply well to Caucasian/white populations, but may apply more poorly to patient of Asian races or other racial backgrounds [ 50 , 51 , 52 ]. Our study only included patients from a single, multi-site institution, which may limit the generalizability of the findings to other practices.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a growing body of literature suggesting that the conventional DXA cutoffs, i.e., t -score > −1.0 for normal bone density, t -score −1.0 to −2.5 for osteopenia/low bone density, and t -score < −2.5 for osteoporosis, may apply differently to different racial backgrounds. Specifically, some groups have suggested that these conventional DXA cutoffs apply well to Caucasian/white populations, but may apply more poorly to patient of Asian races or other racial backgrounds [ 50 , 51 , 52 ]. Our study only included patients from a single, multi-site institution, which may limit the generalizability of the findings to other practices.…”
Section: Discussionmentioning
confidence: 99%
“…There is a case to be made that populations in specific Asian countries or regions may exhibit distinct risk profiles compared to Caucasian populations. Consequently, diagnostic cut-offs and models for fracture prevalence should be more appropriately tailored to these populations [14].…”
Section: Dxa For Bone Quantity Measurementmentioning
confidence: 99%
“…Classical factors associated with osteoporosis that are shared with the general population, including age, lifestyle, nutrition, physical function, genetic, epigenetic, and hormone-dependent factors, should also be considered when assessing bone fragility in a patient with CKD [14]. The coexistence of traditional and non-traditional factors specific to CKD (uremia, acidosis, inflammation, primary kidney disease, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that may also contribute to OP risk and progression include periostin levels associated with endocrine disease [32], the gut microbiota [33,34], anti-Mullerian hormone [35,36], and genetic factors [37], reviewed in [38,39], and mediators such as irisin [40]. Vascular dysfunctions such as varicose veins have also been implicated in the development of OP [41].…”
Section: Variables and Factors Influencing Post-menopause Diseases An...mentioning
confidence: 99%